2002
DOI: 10.1046/j.1440-1746.2002.02661.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol injection therapy of an isolated bile duct associated with a biliary‐cutaneous fistula

Abstract: Bile leakage after hepatic resection often results in the formation of a biliary-cutaneous fistula. Such a fistula, when caused by an isolated bile duct in the remnant liver, can be intractable. We report a successful case of ethanol injection therapy of an isolated bile duct. A 73-year-old man underwent right hepatic resection for hepatocellular carcinoma. Bile leakage occurred after surgery, and the patient developed a biliary-cutaneous fistula. Fistulography revealed an isolated bile duct in the remnant por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 9 publications
(14 reference statements)
1
30
0
Order By: Relevance
“…They suggested that the most effective treatments for type D bile duct injury would be ethanol or fi brin glue injection into the divided bile duct, or reoperation. 1 We considered that our patient had a type D leak, so as a second step, we gave him ethanol injection therapy, [9][10][11] which resulted in a decrease in the amount of drained fl uid, but the bile leakage continued. Yamakado et al 12 reported successfully treating bile leakage by performing selective portal vein embolization, which induces atrophy of hepatocytes and fi brosis, whereby the embolized liver ceases to produce bile.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the most effective treatments for type D bile duct injury would be ethanol or fi brin glue injection into the divided bile duct, or reoperation. 1 We considered that our patient had a type D leak, so as a second step, we gave him ethanol injection therapy, [9][10][11] which resulted in a decrease in the amount of drained fl uid, but the bile leakage continued. Yamakado et al 12 reported successfully treating bile leakage by performing selective portal vein embolization, which induces atrophy of hepatocytes and fi brosis, whereby the embolized liver ceases to produce bile.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al [8] reported a successful treatment of an isolated bile duct for a biliary-cutaneous fistula case with 11 sessions of ethanol infusion. In another report by Kyokane et al [9], the isolated bile duct was treated with 6 sessions of ethanol infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment becomes necessary in cases of isolated duct with leakage and/or external fistula when the natural evolution of the process cannot develop because continuous bile drainage is present and hepatocytes continue to produce bile. A few cases where ethanol injection therapy was used to treat an isolated bile duct with leakage and/or a biliary-cutaneous fistula have been described in adult patients (3)(4)(5). Recently, the successful treatment of a draining isolated intrahepatic biliary duct using alcohol sclerotherapy in a pediatric liver transplant recipient has been reported (6).…”
Section: Discussionmentioning
confidence: 99%